Intellectual Capital Disclosure, Information Asymmetry, Cost of Capital, and Firm Value: Empirical Studies on Indonesian Manufacturers - Gomes I., Nadya Gomes I.; Semuel, Hatane; D., Devie (Master of Management Study Program, Faculty of Business and Economics - Petra Christian University, 2019)
Signaling theory suggests that when high-quality entities signal their potentials such as intellectual capital to the market, its participants (e.g., investors) re-evaluate their worth and make informed decisions therefrom. This paper examines the consequences of intellectual capital disclosures with respect to firm value, information asymmetry, and cost of capital. Voluntary intellectual capital disclosure (ICD, measured in index) affects firm value (FV, measured in Tobin’s Q) through reducing both information asymmetry (IA, measured in bid-ask spread) and cost of capital (COC, measured in weighted average cost of capital). 67 Indonesian manufacturers were purposively selected whose financial reports published in Indonesian Stock Exchange official website and Bloomberg provide the data for the research. A research model is estimated to the data through a partial least square analysis. Results provides substantial evidence on the positive effect of ICD on FV and negative effect on IA; negative effect of IA on FV; negative effect of COC on FV; and positive effect of IA on COC. On a separate analysis, IA is shown to significantly mediate the relationship between ICD and FV.